Investigating the association between urban agriculture and food security, dietary diversity, and nutritional status: A systematic literature review. (May 2015) - Warren, Emily; Hawkesworth, Sophie; Knai, Cécile
Highlights: UA may improve dietary diversity in developing and transitional economies. Evidence suggests that UA may be associated with improved food security. Poor quality and weak study designs hinder interpretation and assessing causation. Abstract: Objective: This literature review seeks to examine the evidence for the association between urban agriculture (UA) and food security, dietary diversity, and nutritional status and clarify the evidence base for its effectiveness at ameliorating some food security challenges faced by urban residents. Design: We searched five databases, five grey literature libraries, and hand-searched reference lists to identify all potentially relevant sources. To be included a paper needed to quantify the impact of UA on food security, dietary diversity, or nutrition status. Papers were screened and quality assessed and data were extracted in duplicate. Setting: Developing and transitional economies. Subjects: Urban farmers, their households, and communities. Results: We identified 11, 192 potentially relevant studies and included 13 papers from 12 unique studies. Studies identified both positive and no associations with UA and food security, and in one study's sub-analysis, negative associations were detected. Weak study designs and methods, incomparable measures, compounded with the finding that food insecure households are more likely to engage in UA, all make interpretations difficult. All studies that measured dietary diversity found a positive association. Most studies found a positive association between engagement in UA and food consumption. Findings for nutritional status were mixed, some showing positive associations for stunting. Conclusion: Poor quality and weak study designs made interpretation difficult and the assignment of causation impossible. The evidence base for UA needs to be strengthened before it can be confidently recommended as a strategy to improve urban food security. We did not however, find any evidence to discourage its use.